Segmentally arranged seborrhoeic keratoses with impending atypia and squamous cell carcinoma in an elderly woman. (29th April 2015) - Livingstone, E.; Hillen, U.; Hafner, C.; Piel, S.; Groesser, L.; Schadendorf, D.; Happle, R.
Summary Epidermal naevi (EN) are considered mosaic disorders. Postzygotic mutations are thought to occur during early embryogenesis. They are usually arranged along Blaschko's lines and tend to be noted either at birth or shortly thereafter. Skin tumours arising on EN are occasionally reported, with ongoing discussion as to whether these are collision tumours or a malignant transformation of the EN. We describe a 76‐year‐old woman with segmentally arranged seborrhoeic keratoses that showed impending atypia and, in one lesion, even overt malignant transformation. In biopsies from various lesions we found FGFR3 and PIK3CA hotspot mutations but there was no consistent pattern of mutations explaining the premalignant or malignant growth. So far it is unclear whether the precancerous changes as noted in this elderly patient can be taken as an unusual manifestation of one of the established types of EN, or whether this may represent a separate disorder that could be called 'SASKIA naevus'. The acronym would stand for segmentally arranged seborrhoeic keratoses with impending atypia.